PEMANFAATAN LIMBAH KULIT PISANG UNTUK MENGHASILKAN PUPUK ORGANIK CAIR (POC): Utilization of Banana Peel Waste to Produce Liquid Organic Fertilizer - Kusna, Kusna Ramdani (Poltekes Kemenkes Tanjungpinang, 2022)
This study aimed to look at the nutrients and micro nutrients contained in the compost of banana peel waste and to utilize the waste of banana peel as a raw material for composting. The study was conducted at Jalan Mulawarman III Number 3 RT 02 RW 01 Kramas Village, Tembalang District, Semarang City. Compost physical quality test results showed that compost was blackish brown and smelled typical of bananas. POC testing was carried out in the laboratory of the Center for Industrial Pollution Prevention Technology (BBTPPI) with the results of C / N ratio of 38.15, Nitrogen (N) 0.009%, Phosfor (P) 0.018%, Potassium 0.543%, Zn <0.249 mg / kg, Cu 0.560 mg / kg and pH 5. The bacterial parameters consisted of Fecal Coliform of 9.2 APM / mL, Salmonella negative / 25ml. BOD and COD parameters were examined at the UPT of the Holy Health Laboratory, the COD examination method was cromosulfuric acid oxidation results > 1,500 mg / l while the BOD examination method was chromium of winkler method with results > 3,000 mg / l. The raw materials used as much as 37 liters produce 1,500 ml of POC. The results of laboratory tests for the parameters of Potassium (K) Copper (Cu), Zinc (Zn), Fecal Coliform and Salmonella meet the requirements of organic compost standards in accordance with SNI number 19-7-30-2004. The C / N Ratio parameter is above the standard of organic compost while Nitrogen, Phosphorus (P), and pH are below the standard of organic compost. Additional parameters examined are BOD and COD. Banana skin can be used as raw material for making POC.